Wireless battery charger - Mohamed Noor, Mohamed Yassin (2016)
The aim of the project is to design and develop a wireless battery charger, which has the ability to charge rechargeable batteries for different types of applications. The ambitions of the project are to explore new charging technology such as wireless charging technology in the hope of omitting the usage of charging cables for charging electronic device’s batteries, electric vehicles applications and to transform the wireless charging solution into a common platform for all different types of applications in wide array of environments.